2008
DOI: 10.1038/oby.2008.283
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Variation in the FTO Gene on Whole Body Fat Distribution, Ectopic Fat, and Weight Loss

Abstract: Recent genome-wide association studies aiming to identify genes responsible for diabetes mellitus described a strong link between variations in the FTO (fat mass-and obesity-associated) gene and body weight (1,2). The association with obesity is replicable in most populations (3)(4)(5), but the mechanism how variants in FTO lead to obesity is still not completely understood.FTO was originally described in a mouse model and is involved in cell death programming (6). In heterozygote mice, the mutation results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
89
2
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 24 publications
13
89
2
7
Order By: Relevance
“…Our finding of no main effects of FTO rs9939609 on change in anthropometrics and metabolic estimates during intervention is in agreement with the two studies. 21,22 Other studies than the present are suggestive of modifiable effects of FTO variants. 5,33 Unfortunately, it was not possible to examine the interaction between genotype and fat and CHO content in either of the two previous studies of FTO variants and response to weight loss intervention.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Our finding of no main effects of FTO rs9939609 on change in anthropometrics and metabolic estimates during intervention is in agreement with the two studies. 21,22 Other studies than the present are suggestive of modifiable effects of FTO variants. 5,33 Unfortunately, it was not possible to examine the interaction between genotype and fat and CHO content in either of the two previous studies of FTO variants and response to weight loss intervention.…”
Section: Discussionsupporting
confidence: 44%
“…32 Two previous studies have examined FTO variants in relation to weight loss interventions. 21,22 Unfortunately, drop out from the interventions was not analysed in either of these reports. Our finding of no main effects of FTO rs9939609 on change in anthropometrics and metabolic estimates during intervention is in agreement with the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…articles Genetics variants are associated with overall body fat mass and ectopic fat storage in the liver (15).…”
mentioning
confidence: 99%
“…We demonstrated that only SNPs in the FTO gene are associated with SFA and BMI, but not with VFA. FTO rs8050136 has been shown to be marginally associated with visceral fat mass measured by magnetic resonance imaging in Germany (P¼0.05) 36 and rs9939609 with intra-abdominal adipose tissue estimated by dual energy X-ray absorptiometry in Danish (P¼4.7Â10 À3 ). 37 SNP rs8050136 has been reported to be marginally associated with VFA measured by CT in African Americans (P¼0.05), but not in Hispanic Americans.…”
Section: Discussionmentioning
confidence: 99%